Decade-long isotope dataset (δ2H and δ18O) of rainfall and non-rainfall water samples in the central Namib Desert, Namibia - Li, Yue; Marais, Eugene; Wang, Lixin (PANGAEA, 2025)
The long-term rainfall and non-rainfall (i.e., fog and dew) water samples were collected at the Gobabeb - Namib Research Institute in the central Namib Desert, Namibia (-23°33′39.3″S, 15°02′24.6″E) between 2014 and 2023. This research institute is situated on the outer edge of the Namib fog zone, where visible fog is present along the Namib coast, about 60 km from the South Atlantic Ocean (Eckardt et al. (2013, doi:10.1016/j.jaridenv.2012.01.011; Kaseke et al. (2017, doi:10.1175/1520-0450(1994)033)). The Gobabeb - Namib Research Institute is located downstream of the Kuiseb River catchment, which flows from the eastern Knomas Highland to western Walvis Bay. The climate at Gobabeb is hyper-arid, with a multi-year (1962-2022) average annual rainfall of 30.5 mm and a multi-year (1966.1-2003.12 and 2006.10-2022.12) average annual fog amount of 112.1 mm. In addition, the spatial fog samples were collected from 13 stations across the central Namib Desert during two periods: June 10−19, 2016, and June 27-July 10, 2017. The 13 stations include Coastal MET, Kleinberg, Soophies Hoogte, Marble koppie, Vogelfederberg, Station 8, Aussinanis, Gobabeb, Station 1, Station 2, Station 3, Station 4, and Station 5. The 13 stations collectively covered an area of approximately 1,700 km², with a complete roundtrip visit spanning about 250 km (Kaseke et al. (2018, doi:10.4209/aaqr.2017.01.0062)). Before each roundtrip field campaign, we inspected the fog collector at the Gobabeb-Namib Research Institute and monitored real-time meteorological data (leaf wetness and relative humidity) from other stations to identify fog events across the central Namib Desert. If fog was present, we immediately conducted sampling roundtrips to all 13 sites using alternating routes (Gobabeb-Aussinanis-Coastal MET-Gobabeb). The Standard Fog Collectors (SFCs), designed according to Schemenauer and Cereceda (1994), were used to collect event-scale (i.e., daily) fog water samples for isotopic analysis. All the captured fog water ran down from the bottom of the collectors into a 1 L glass bottle anchored to the ground through a pipe sealed at both ends to minimize water evaporation. After fog water sample collections in the morning, they were transferred into a 15 ml Qorpak French square bottle and sealed with a Black Phenolic Pulp/Vinyl Lined Cap. Dew was captured using a dew collector consisting of a 1 m² metal sheet covered by a glass plate, inclined at 30° and elevated 0.5 m above the ground. The glass plate cools to or below the dew point, enabling condensation to form and accumulate in a trough at its lower edge. A connected pipe channels the collected moisture into a storage container. When water was collected in the dew collector and absent from the fog collector this input was classified as dew. To minimize evaporation effects, all dew samples were collected before dawn. The rainfall samples were collected using a Young Model 52202 tipping-bucket rain gauge. All rainfall samples were collected immediately after each event or, if the event ended after midnight, at the earliest possible time in the morning (Tian et al. (2021, doi:10.1016/j.jhydrol.2020.125847)). If multiple rainfall events occurred in a single day, we collected samples from each event separately to eliminate evaporation effects on water samples. All the water samples were stored in the refrigerator at the Gobabeb - Namib Research Institute until shipment to the Indiana University Indianapolis Ecohydrology Lab for isotope analysis. A Los Gatos Research Inc GLA431 series analyser (Los Gatos Research Inc., Mountain View, CA, USA) was utilized to measure the stable isotopic composition (δ2H and δ18O) of fog, rain, and groundwater samples over the study period. The majority of temporal event-based fog water samples at the Gobabeb - Namib Research Institute was opportunistically and equably sampled across seasons throughout the study period (2014-2023). The annual fog water sampling coverage exceeded 65% throughout the study period. We made every effort to opportunistically and comprehensively collect rainfall and dew samples at the Gobabeb–Namib Research Institute between 2014 and 2023. These observational isotope datasets in the central Namib Desert, Namibia provide valuable insights into the processes governing dryland water cycle patterns and their responses to global climate change.
Keywords: dew water; fog water; isotope composition; Namib Desert; rainfall